Participatory system dynamics modelling for housing, energy and wellbeing interactions. Issue 7 (3rd October 2018) - Eker, Sibel; Zimmermann, Nici; Carnohan, Shane; Davies, Mike
ABSTRACT: The built environment is a key target of decarbonization policies. However, such policies often have a narrow objective and narrow focus, resulting in 'policy-resistance' and unintended consequences. The literature attributes these unintended consequences to a narrow financial focus, adverse incentives, and inadequate handling of knowledge, skills, communication and feedback gaps, but it provides little advice on how these complex interactions can be captured. This paper illustrates the development and application of an integrated approach to address these complex interactions with regard to housing performance, energy, communal spaces and wellbeing. In particular, it explores the dynamics created by these relationships with simulation modelling in participatory settings, and with a diverse group of stakeholders. The simulation results suggest that monitoring is key to improve the performance of the housing stock besides energy efficiency; and investments in communal spaces positively affect the adoption of energy-efficiency measures and the wellbeing of residents. The evaluation results for participatory workshops show this approach was found useful by the stakeholders for supporting more integrated decision-making about housing. In future research, this approach can be implemented for policy problems in specific contexts.